Performance characteristics of Paralympic swimming - Fulton, S.; Pyne, D.; Burkett, B. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
Introduction Margins of victory in elite swimming competitions are often small and are influenced by the performance characteristics of the athlete. This thesis examined variability and progression in competition times, training characteristics, and the contribution of kicking to Paralympic swimming performance. Studies Annual improvements in competitive performance of 1-2% which account for variability (~1.3%), progression (~0.5%) and the level of a competition (~1.5%) are required for top-ranked Paralympic swimmers to substantially increase medal prospects. Improvements of this magnitude require an effective training program. Training volume and intensity were quantified for 16 Paralympic swimmers, 16 weeks prior to a World Championship. Increases in main-set training volume (~24, ±19%: mean, ±90% confidence limits) and perceived exertion (~7, ±3%) were observed mid-season prior to substantial reductions in volume (~24, ±18%) and maintenance of intensity during the taper. There was no clear association between training volume and functional ability of the swimmers, or between training measures and performance. Kick sets were prescribed in the majority of the training sessions though lap time was the only quantifiable variable. The characteristics of a swimmer`s kick are unknown. The kick is partially obscured by turbulence and therefore difficult to measure. Kick count and kick rate validity and reliability were established by the novel use of inertial sensors attached to the legs. Kicking patterns were then measured for 14 Paralympic swimmers in 100 m freestyle swimming time trials. Kick count did not change within a trial though substantial decreases in kick rate (~12, ±1%) were observed by the 3rd 25 m segment. The relationship between swimming and kickingonly kick rates was r = 0.67 (0.55 to 0.76). Some swimmers have a better transfer of kick rate from kicking-only to swimming than others. The influence of kicking velocity and amplitude on net force and kick rate were investigated in 12 Paralympic swimmers using a dynamometer and force platform system. The net force naturally increased with a faster tow velocity (~24, ±5%), without a concomitant increase in kick rate that remained largely unchanged at ~150 kicks·min-1 for all velocities. Deep amplitude kicking substantially decreased kick rate (~14, ±5%) and increased force (~10, ±5N). This relationship between kick rate, velocity, amplitude and net force provides insight into guidelines for the prescription of kick training. Discussion/Conclusion The key for Paralympic swimmers is to implement kick rates and amplitudes, complementary to the arm stroke, that elicit faster swimming velocities with a relative decrease in net towing force. Coaches and swimmers should address issues of variability and progression in competition times and training and kicking characteristics, to enhance competitive Paralympic swimming performance.